Tumour necrosis factor synergises with gamma interferon on the induction of mRNA for DR alpha chain on thyrocytes from Graves' disease and non toxic goitre. - Kissonerghis, A; Grubeck-Loebenstein, B; Pirich, K; Feldmann, M; Londei, M (Informa Healthcare, 1989)
In both thyroid autoimmune diseases Graves' and Hashimoto's thyroiditis, the epithelial thyroid follicular cells (TFC) have been shown to express HLA class II molecules, and can restimulate autoreactive T cells cloned from the diseased tissue. This aberrant class II expression is important in the mechanism of perpetuation of the disease process, therefore we have compared the effect of interferon gamma (IFN gamma) and tumour necrosis factor (TNF alpha) on the HLA-DR alpha mRNA expression of thyroid follicular cells derived from Graves' disease (GD) and a non autoimmune disease, non toxic goitre (NTG). Our results indicate that TNF alpha synergises with IFN gamma in the induction of HLA class II mRNA. There was no consistent difference in DR alpha mRNA expression between the GD and NTG thyroid follicular cell preparations in response to induction by a combination of these lymphokines at various concentrations. Our data suggest that the differences in the level of expression of class II molecules observed in vivo in Graves' disease and non toxic goitre, which is much higher in the former, is probably due to local release of lymphokines by infiltrating T lymphocytes, although other factors may be involved.